The oversight of autonomous artificial intelligence: lessons from nurse practitioners as physician extenders. Issue 2 (11th August 2022) - Morrell, Walker; Shachar, Carmel; Weiss, Anthony P
Abstract: The development of autonomous artificial intelligence (A-AI) products in health care raises novel regulatory challenges, including how to ensure their safety and efficacy in real-world settings. Supplementing a device-centered regulatory scheme with a regulatory scheme that considers A-AI products as a 'physician extender' may improve the real-world monitoring of these technologies and produce other benefits, such as increased access to the services offered by these products. In this article, we review the three approaches to the oversight of nurse practitioners, one type of physician extender, in the USA and extrapolate these approaches to produce a framework for the oversight of A-AI products. Under the framework, the US Food and Drug Administration would evaluate A-AI products and determine whether they are allowed to operate independently of physician oversight; required to operate under some physician oversight via a 'collaborative protocol' model; or required to operate under direct physician oversight via a 'supervisory protocol' model.